Microstructure evolution and softening mechanism of Ti-55511 alloy with equiaxed structure during sub β-transus hot deformation - Shuangxi Shi; Jinyang Ge; Xiaoyong Zhang; Yaobiao Liang; Qixing Liu (Journal of Materials Research and Technology)
Microstructure evolution behavior and softening mechanism of Ti-55511 alloy during sub β-transus hot deformation were systematically investigated. The results show that the deformation parameters greatly affect the dynamic softening behavior of α and β. Among them, either increasing the temperature or significantly increasing the strain rate favor the DRX of the α phase. The aspect ratio of the equiaxed α gradually increases during early stages of hot deformation, and the α phase is elongated to form the lamellar-like structure. Subsequently, its inner interface gradually migrate and transform, which is accompanied by the wedging of the β phase and dynamic globalization of the α phase, leading to the refinement of α grains. For β, the main softening mechanism is DRV. However, increasing the deformation temperature and decreasing the strain rate can promote DRX of the β phase. Its DRX is accomplished by the progressive sub-grains rotation, which increases their misorientation and thus facilitates the LAGB to HAGB transition, a typical CDRX. The equiaxed α grains promote nucleation of β recrystallized grains at the α/β phase interface.